Evaluation of Tomato-Based Packing Material for Retention of Ammonia, Nitrous Oxide, Carbon Dioxide and Methane in Gas Phase Biofilters: A Laboratory Study - Pereira, José L.S. (2022)
Biofilters are an effective air pollution control technology to break down gaseous contaminants and produce innocuous end products. This laboratory study aimed to evaluate a biofilter media, mainly composed by tomato waste, as packing material to reduce NH3, N2O, CO2 and CH4 losses from stored pig slurry. Three mixtures of packing materials, with and without oxalic acid, were arranged in treatments, namely: mixture of tomato waste, pine bark and agricultural compost; mixture of tomato waste and rice husk; tomato waste only. A control treatment (no biofilter) was also included. The experiments were conducted using a system of laboratory scale biofilters connected to jars filled with pig slurry and under a constant airflow rate. The gas concentrations were measured for 14 days and the physicochemical of the packing materials were assessed. Results showed that biofilter media mixtures had a potential for NH3 retention ranging from 51 to 77% and the addition of oxalic acid to these biofilters increased NH3 retention to 72–79%. Additionally, the biofilter media mixtures with and without oxalic acid showed a potential retention for CH4 (29–69%) but not for N2O, yet with no impact on the global warming potential. It can be concluded that tomato based biofilters had the potential to reduce gaseous emissions from slurry.